Compressive and Tensile Capacity of Recycled Aggregate Concrete (RAC) with Glass as Supplement Material - Adnan, Suraya Hani; C. Shen, Tic; Wan Ibrahim, Mohd Haziman; Jamaluddin, Norwati (International Journal of Integrated Engineering, 2013)
The amount of construction waste is increased significantly over the years due to reconstruction and the demolition of old buildings. One of the major challenges of our present society is to protect the environment by recycling the existing construction waste. This study concerned on two types of variable in the production of concrete which are the utilization of coarse recycled aggregate and utilization of different supplement ratio of fine glass wastes to cement. To evaluate the viability of this study, an experimental work was performed in order to monitor the mechanical behavior of such concrete. The compression and splitting tensile strength of concrete were determined on this study. From the result, it is conclude that the utilization of recycled aggregate does not much affect in the uniaxial compressive strength and splitting tensile strength of concrete, for replacement ratio up to 25 %. However, the utilization of fine glass as supplement material to cement is increase the uniaxial compressive and splitting tensile strength of concrete, for supplement ratio up to 5 %. Thus, it can be stated that the optimum concrete mixture is the mixture of 25 % recycled aggregate and 5% glass.